2014
DOI: 10.1136/heartjnl-2014-306067
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural imaging and outcomes after catheter ablation of atrial fibrillation

Abstract: Objective Catheter ablation of atrial fibrillation (AF) has become an increasingly safe and effective therapy. This has been partly attributed to the use of adjunctive imaging modalities. We aimed to describe the use and associated outcomes of periprocedural imaging for AF ablation. Methods We studied all Medicare fee-for-service claims for AF ablation from July 2007 to December 2009, and identified associated imaging studies before and during ablation, including transoesophageal echocardiography (TEE), intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
3
11
0
1
Order By: Relevance
“…An integrated 3D scar reconstruction from delayed gadolinium-enhanced MR imaging was used to facilitate ventricular tachycardia ablation [82] and to confirm/deny the presence of scar after the intervention. Furthermore, there has been increasing interest in visualizing the immediate post ablation injury to better understand its effect on left atrium remodeling and the success of the procedure [83]. Within 24 hours after ablation, dark regions of no-reflow on contrast enhanced MR imaging have been used to correlate with regions of myocardium that eventually become scarred [84,85].…”
Section: Appearance Of Treated Tissues On Mr Imagingmentioning
confidence: 99%
“…An integrated 3D scar reconstruction from delayed gadolinium-enhanced MR imaging was used to facilitate ventricular tachycardia ablation [82] and to confirm/deny the presence of scar after the intervention. Furthermore, there has been increasing interest in visualizing the immediate post ablation injury to better understand its effect on left atrium remodeling and the success of the procedure [83]. Within 24 hours after ablation, dark regions of no-reflow on contrast enhanced MR imaging have been used to correlate with regions of myocardium that eventually become scarred [84,85].…”
Section: Appearance Of Treated Tissues On Mr Imagingmentioning
confidence: 99%
“…79 They found that use of preprocedural cardiac CT/MR was associated with a lower risk of TIA/stroke at 6 months (0.4% vs 0.9%, adjusted HR 0.46). Use of ICE was found to be associated with higher risk of bleeding (1.1% vs 0.7%, adjusted HR 1.76), but also with a lower incidence of repeat ablation (5.7% vs 8.5%, adjusted HR 0.68).…”
Section: Peri-procedural Imaging In Catheter Ablationmentioning
confidence: 99%
“…Figure 7 Temporal trends of imaging usage before (CT, MRI, TOE) and during (ICE) ablation. 79 ICE, intracardiac echocardiography.…”
Section: Anticoagulation For Stroke Prevention Which Antithrombotic Tmentioning
confidence: 99%
“…11 The clear benefit of ICE over 3DRA is that it allows continuous realtime visualisation of geometry and catheter …”
Section: Intracardiac Echocardiographymentioning
confidence: 99%